Analysis of Gross Tonnage (GT) Capacity Installed On Traditional Wooden Ships In Penajam Paser Utara - Manik, Aljoiden; Arifuddin, Andi Mursid Nugraha; Pawara, Muhammad Uswah; Nurcholik, Samsu Dlukha; Ikhwani, Rodlian Jamal (Naval Architecture Department, Kalimantan Institut of Technology, 2023)
To identify the GT of traditional wooden boats built at PPU, an investigation of the GT on the boat is carried out. The GT of the North Penajam Paser traditional wooden ship was identified using domestic regulations issued by the government through the Ministry of Transportation, PM No. 45 of 2021 and PP No. 85 of 2021 concerning PNBP of the Directorate General of Sea Transportation. Before being operated, every ship must be measured to determine the length, width, depth and tonnage of the ship in accordance with the ship measurement method. According to Law number 20 of 1997,